Extended biotic ligand model for predicting combined Cu–Zn toxicity to wheat (Triticum aestivum L.): Incorporating the effects of concentration ratio, major cations and pH. (November 2017) - Wang, Xuedong; Ji, Dongxue; Chen, Xiaolin; Ma, Yibing; Yang, Junxing; Ma, Jingxing; Li, Xiaoxiu
Abstract: Current risk assessment models for metals such as the biotic ligand model (BLM) are usually applied to individual metals, yet toxic metals are rarely found singly in the environment. In the present research, the toxicity of Cu and Zn alone and together were studied in wheat ( Triticum aestivum L.) using different Ca 2+ and Mg 2+ concentrations, pH levels and Zn:Cu concentration ratios. The aim of the study was to better understand the toxicity effects of these two metals using BLMs and toxic units (TUs) from single and combined metal toxicity data. The results of single-metal toxicity tests showed that toxicity of Cu and Zn tended to decrease with increasing Ca 2+ or Mg 2+ concentrations, and that the effects of pH on Cu and Zn toxicity were related not only to free Cu 2+ and Zn 2+ activity, respectively, but also to other inorganic metal complex species. For the metal mixture, Cu–Zn interactions based on free ion activities were primarily additive for the different Ca 2+ and Mg 2+ concentrations and levels of pH. The toxicity data of individual metals derived by the BLM, which incorporated Ca 2+ and Mg 2+ competition and toxicity of inorganic metal complexes in a single-metal toxicity assessment, could predict the combined toxicity as a function of TU. There was good performance between the predicted and observed effects (root mean square error [ RMSE ] = 7.15, R 2  = 0.97) compared to that using a TU method with a model based on free ion activity ( RMSE  = 14.29, R 2  = 0.86). The overall findings indicated that bioavailability models that include those biochemistry processes may accurately predict the toxicity of metal mixtures. Graphical abstract: Highlights: Increasing activity of Ca 2+ and Mg 2+ will decrease Cu or Zn toxicity. The increase of Cu or Zn toxicity with increasing pH is due to change of Cu or Zn species. The Cu–Zn interactions showed additive effects for different Ca, Mg and pH sets. We model combined toxicity of Cu–Zn mixtures using the biotic ligand model based TU approach. The extended BLM demonstrate good performances in predicting the combined toxicity of Cu–Zn mixtures. Abstract : We developed an extended biotic ligand model, which took account of the effect of solution characteristics, and accurately predicted Cu–Zn mixture toxicity to wheat.